Nootka totem pole in front of City Hall at Yellowknife, NWT ... - Campbell, Sandy (University of Alberta Library, 2015)
This totem pole stands near the avenue in front of City Hall in Yellowknife, NWT. It was carved at Nitinhat, B.C., by carver, Frank Knighton and donated in 1971 by the People of British Columbia. ...